ANALISIS SIKAP KONSUMEN TERHADAP MINUMAN KALENG NESCAFE DI PASAR BAWAH PEKANBARU - Raka Prasetyo; Novia Dewi; Ermi Tety (Indonesian Journal of Agricultural Economics, 2021)
This research was aimed to analyze consumer attitudes toward Nescafe canned drink in the scope of Pasar Bawah and the surrounding area. This research was conducted from May to June 2018 using survey and questionnaire method to 30 respondents. Respondents are people who buy Nescafe canned drink. There are 27 male and 3 female based on gender. Data of customers attitude was analyzed using “multidimensional scaling” in SPSS application. The research found that costomers preferred Nescafe Latte than other flavor canned drink